Feasibility, acceptability, and preliminary efficacy protocol of an intervention for caregivers of hospice patients living with dementia: A pilot randomized control trial - Ebtesam Tamer; Donald R. Hoover; Margaret V. McDonald; Kira G. Sheldon; Felix Vasquez; Maryam Gaibi; Elizabeth A. Luth (PLoS ONE, 2025)
Introduction Caring for dying persons living with dementia (PLwD) poses substantial challenges for family care partners (FCPs), who often experience significant emotional and physical strain. Home hospice provides support to enable home death, including support for FCPs. We are pilot testing a home hospice intervention (Enhancing Dementia Instruction and Tool in Home Hospice Care (EDITH-HC)) to reduce FCP burden and improve care for PLwD. This pilot test assesses feasibility, acceptability, and preliminary efficacy using a non-blinded randomized clinical trial (RCT). Methods We aim to match 24 hospice nurses and social workers (“clinicians”) with 96 FCPs of home hospice PLwD. Clinician teams are randomized to the intervention or control condition using an adaptive randomized strategy to maintain balance between Black and White FCPs in each study arm. The intervention consists of educational videos to enhance clinicians’ knowledge about and confidence in providing dementia-specific end-of-life care and a tool for clinicians to use with FCPs to identify and address FCPs’ dementia-related stressors. Participants answer online or telephone surveys at baseline, following each of four routine home visits, and post-intervention. We will compile descriptive statistics to report on feasibility and acceptability measures. We will conduct t-tests of differences and linear regression analyses to examine differences in FCP burden (primary outcome) between baseline and first subsequent clinician visit (primary time point). Additional exploratory analyses are explained. Results We have enrolled 29 clinicians and 53 FCPs and aim to have 24 clinicians matched with 96 FCPs (N = 120) to complete the intervention. Discussion If the pilot shows positive results for the intervention, we plan to test it in a multi-site, fully-powered RCT. Enhancing support for clinicians and FCP of PLwD could optimize FCP and hospice patient outcomes.